The Bactericidal Activity of Protein Extracts from Loranthus europaeus Berries: A Natural Resource of Bioactive Compounds - Rosa Luisa Ambrosio; Lorena Gratino; Sara Mirino; Ennio Cocca; Antonino Pollio; Aniello Anastasio; Gianna Palmieri; Marco Balestrieri; Angelo Genovese; Marta Gogliettino (MDPI AG, 2020)
Loranthus europaeus is a well-known and important medicinal plant, with a long history of traditional medicine use. Several studies showed that it contains many bioactive compounds with a wide range of pharmacological effects. In light of these past researches, L. europaeus were chosen to consider its potential antimicrobial action. To this aim, different protocols were performed to selectively extract protein compounds, from L. europaeus yellow fruits, and evaluate the antimicrobial activity against four phytopathogenic fungi (Aspergillus niger, Alternaria spp., Penicillium spp., Botritis cinereus) and a number of foodborne bacterial pathogens (Listeria monocytogenes, Staphylococcus aureus strains, Salmonella Typhimurium and Escherichia coli) by using serial dilutions and colony formation assays. Results evidenced no antifungal activity but a notable bactericidal efficiency of a crude protein extract against two foodborne pathogens, with minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values between 0.2 and 0.5 mg/mL, being S. aureus strains the most susceptible bacteria. Moreover, a strong bactericidal activity against S. aureus M7 was observed by two partially purified protein fractions of about 600 and 60 kDa molecular mass in native conditions. Therefore, these plant protein extracts could be used as natural alternative preventives to control food poisoning diseases and preserve foodstuff avoiding health hazards of chemically antimicrobial applications.